Bitcoin as hedging alternatives from gold, stocks and USD - GARCH model for risk/volatility analysis - Kua, Kim Tai (2024)
There is increased interest in the capability of cryptocurrency as investment instrument, especially interest on Bitcoin which classified as “digital gold”. This paper sets out to examines the hedging performance of gold, S&P 500, Nasdaq and USD (USDX) against fluctuations in Bitcoin prices. Furthermore, this study compares four alternative regression specifications for estimating the optimal hedge ratio and measuring the hedge effectiveness: Single Equation Method Ordinary Least (SEMOLS), Bivariate Vector Autoregression (VAR), Vector Error-Correction Method (VECM) and CCC- MGARCH models.